Primenenie iskusstvennogo intellekta dlia povysheniia effektivnosti reklamnykh kommunikatsii - Zaitsev O. N. (Modern science and education: choosing the future, 2024)
This paper investigates how artificial intelligence (AI) technologies are used in improving the advertising communications effectiveness. The authors analyze how the use of AI can affect the advertising campaign effectiveness, and also consider the potential application of AI in the global advertising market. The object of the study is advertising communications of commercial enterprises. The subject is using AI in advertising communications. This article attempts to identify and characterize the directions of using artificial intelligence in advertising communications to improve their effectiveness. To achieve this goal, the following tasks are supposed to be solved: to identify opportunities to improve the effectiveness of targeting using AI; to consider the AI use to create unique advertising content (generation of texts, images and video content); to identify opportunities to analyze large amounts of data on the behavior and preferences of the target audience, its segmentation and, accordingly, the creation of personalized advertising messages; to consider the possibilities of providing personalized support for communications with customers using AI in advertising communications. As a result of the study, the authors offer a definition and characteristics of the main directions for using artificial intelligence in advertising communications.
Keywords: искусственный интеллект; маркетинг; marketing; artificial intelligence; advertising communications; personalized messaging; targeting effectiveness; рекламные коммуникации; персонализированные месседжи; эффективность таргетинга